The assessment of scattered light in ophthalmic materials. Issue 4 (27th May 2015) - Dain, Stephen J.; Yuen, Gloria S‐C.
Abstract: The assessment of scattered light in lenses, sunglasses and eye protection has been carried out in various ways. Wide‐angle scatter (haze) is used in the United States, Australia and New Zealand. Small‐angle scatter (light diffusion) is specified in Europe. Little is known of the relationships within and between the methods. In an international standard, a single method is generally required. The measurement of wide‐angle scatter (haze) (two variations of a method) and small‐angle scatter (light diffusion) (three variations of a method) were carried out on 12 samples, 4 abraded, 4 with inclusion defects and 4 with surface coating defects, in an international inter‐laboratory comparison. The consensus means and confidence limits were used to compare two haze methods: the "Basic" light diffusion method and two variations of the "Simplified" light diffusion method. For abraded samples, haze and light diffusion measures are linearly related. For the remaining samples, the haze method was a much more sensitive detector of low levels of light scatter. The three measures of light diffusion are highly linearly correlated. Haze is the more sensitive measure for lower levels of light scatter when due to smaller scattering elements. The Basic and Simplified methods are highly linearly correlated. The red laser Simplified method returns a value 10% lower than that of the Basic method, and the green laser Simplified method returns a value 12% higher than that of the Basic method. These can be accounted for by a calibration factor or different acceptance values. © 2015 Wiley Periodicals, Inc. Col Res Appl, 41, 416–423, 2016